Light valve, light valve manufacturing method and dimming glass assembly
By adding solid additives to the light-controlled layer matrix emulsion of the dimming film, the compressive performance problem of the dimming film under high temperature and high pressure conditions is solved, and its compressive strength is significantly improved, meeting the preparation requirements of dimming glass components.
Patent Information
- Application Number
- CN202110872125.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-07-30
AI Technical Summary
The color discoloration performance of the dimming film is easily damaged during the lamination process of high temperature and high pressure, which is mainly due to the poor compressive resistance of the light control layer, which makes it difficult to prepare the dimming glass components.
The addition of solid additives, such as solid particles, rods and fibers, to the light control layer matrix emulsion, enhances the compressive resistance of the light control layer. These solid additives are distributed in the polymer matrix to form a structure containing suspended medium droplets and solid light-controlled particles.
The compressive strength of the light control layer is significantly improved by adding solid additives, reducing the color discoloration performance damage of the dimming film under high temperature and high pressure conditions, and meeting the lamination process requirements of dimming glass components.
Smart Images

Figure CN113568196B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electronic light-controlling materials, and in particular to a light valve and a manufacturing method thereof. Background Art
[0002] Light valve is a new type of electronic light control product. It mainly sets a light control layer between two layers of transparent electrodes. When the electric field is turned on, the arrangement or state of the material in the light control layer changes, so that the light transmittance characteristics of the overall dimming film change, such as from opaque to transparent, or from transparent to opaque. Through the action of the electric field, it can achieve rapid conversion between the on-state and the off-state. According to the different light control mechanisms of the light control layer, light valves can be divided into suspended particle light valves, polymer dispersed liquid crystal light valves, electrochemical reaction dimming valves, etc.
[0003] According to the different substrates of the light valve, there are light valves with plastic sheets such as PET as the substrate, which are called dimming films, and light valves with glass as the substrate, which are called dimming glass. The structure of sandwiching the dimming film between two glass plates is called a dimming glass assembly.
[0004] As for the dimming film, in practical applications, the dimming film is often sandwiched between two pieces of glass and laminated under a certain temperature and pressure to form a dimming glass component. However, the color-changing performance of the dimming film is often greatly damaged during the high-temperature and high-pressure lamination process. The main reason is that the compressive performance of the light-controlling layer of the dimming film is poor under high temperature, which makes it very difficult to prepare the dimming glass component.
[0005] The prior art dimming film cannot effectively solve the problem of poor compressive performance of the light control layer of the dimming film under high temperature. Summary of the invention
[0006] To solve the above problems, the present application provides a light valve, comprising:
[0007] a first transparent substrate,
[0008] a first transparent electrode formed on a first transparent substrate,
[0009] The second transparent substrate,
[0010] A second transparent electrode is formed on a second transparent substrate, the first transparent electrode and the second transparent electrode are arranged opposite to each other, and
[0011] A light control layer is disposed between the first transparent electrode and the second transparent electrode; the light control layer comprises a polymer matrix;
[0012] Wherein, the polymer matrix is dispersed with suspension medium droplets, and the suspension medium droplets are distributed with solid light-controlling particles.
[0013] Solid additives capable of enhancing the compressive resistance of the light control layer are also distributed in the polymer matrix.
[0014] Preferably, the solid additive includes at least one of solid particles, solid rods and solid fibers.
[0015] Preferably, the shape of the solid additive includes at least one of a regular shape and an irregular shape.
[0016] Preferably, the solid particles include at least one of spherical solid particles and polyhedral solid particles.
[0017] Preferably, the spherical solid particles include at least one of oxide microspheres and polymer microspheres.
[0018] Preferably, the solid fiber comprises at least one of glass fiber and polymer fiber.
[0019] Preferably, the maximum straight-line distance between two points on the surface of the solid particle is less than 50 microns.
[0020] Preferably, the maximum straight-line distance between two points on the surface of the solid particle is less than 20 microns.
[0021] Preferably, the spherical solid particles are microspheres with a diameter of 0.1 micrometer to 50 micrometers.
[0022] More preferably, the spherical solid particles are microspheres with a diameter of 0.5 micrometers to 20 micrometers.
[0023] More preferably, the spherical solid particles are microspheres with a diameter of 1 micron to 15 microns.
[0024] Preferably, the mass of the solid additive accounts for 0.01% to 6% of the mass of the light control layer matrix emulsion.
[0025] More preferably, the mass of the solid additive accounts for 0.03% to 4% of the mass of the light control layer matrix emulsion.
[0026] More preferably, the mass of the solid additive accounts for 0.08% to 2% of the mass of the light control layer matrix emulsion.
[0027] Preferably, the polymer matrix is a siloxane copolymer.
[0028] Preferably, the material forming the suspension medium droplets includes at least one of fluorocarbon organic compounds, phthalates, trimellitates, dodecylbenzene, polybutene oil, polyacrylate, polymethacrylate, epoxidized soybean oil, and epoxidized linseed oil.
[0029] Preferably, the solid light-controlling particles include at least one of oxide nanorods, perovskite nanorods, and polyiodine compound nanorods.
[0030] Preferably, the first transparent electrode comprises ITO, nano-Ag wire, graphene, nano-Cu wire; the second transparent electrode comprises one of ITO, nano-Ag wire, graphene, nano-Cu wire.
[0031] Preferably, the first transparent substrate and the second transparent substrate comprise glass plates.
[0032] Preferably, the first transparent substrate and the second transparent substrate comprise transparent plastic sheets.
[0033] Preferably, the first transparent electrode and / or the second transparent electrode may be covered with an insulating layer.
[0034] In addition, the present application also provides a dimming glass assembly, comprising
[0035] The first glass plate and the second glass plate are provided with the light valve between the first glass plate and the second glass plate; wherein: a first interlayer is provided between the first glass plate and the light valve, and / or a second interlayer is provided between the second glass plate and the light valve.
[0036] In addition, the present application also provides a method for manufacturing the above light valve, comprising:
[0037] Providing solid light-controlling particles;
[0038] providing a suspension medium;
[0039] Mixing the solid light-controlling particles with the suspension medium to form a suspension medium mixture containing the solid light-controlling particles;
[0040] providing a polymer matrix precursor;
[0041] Mixing an initiator for initiating crosslinking and curing of the polymer matrix precursor, the suspension medium mixture containing solid light-controlling particles, the polymer matrix precursor and a solid additive to obtain a light-controlling layer matrix emulsion;
[0042] Applying the light control layer matrix emulsion on the first transparent electrode of the first transparent substrate to form a light control layer wet film;
[0043] Covering the light control layer wet film with a second transparent electrode of a second transparent substrate;
[0044] The light control layer wet film is cross-linked and cured to obtain the light valve.
[0045] The inventors have found that the effect of increasing the compressive strength of the light-controlling layer is unexpectedly significant by adding a solid additive during the process of forming the light-controlling layer matrix emulsion. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0047] Figure 1 Schematic diagram of the structure of the dimming film provided in some embodiments of the present invention, wherein 3 is a transparent substrate, 1 is a transparent electrode, 2 is a light control layer, 21 is a polymer matrix, 22 is a suspension medium droplet containing solid light control particles, 23 is a solid light control particle, and 24 is a solid additive. DETAILED DESCRIPTION
[0048] See Figure 1 The polymer matrix precursor contains cross-linkable and curable functional groups, and is cured through a cross-linking reaction to form a polymer matrix 21.
[0049] The suspension medium is dispersed in the polymer matrix in the form of droplets, and the formed droplets are called suspension medium droplets 22.
[0050] Example 1 Preparation of solid light-controlling particles 23
[0051] Add 30g of isoamyl acetate solution containing 21.2wt% nitrocellulose (model SS 1 / 4sec), 6g I2, 70g isoamyl acetate and 4g anhydrous CaI2 to a 250mL three-necked round-bottomed glass flask, and heat to 42°C. After I2 is dissolved, add 6g anhydrous methanol, 0.8g distilled water and 4g 2,5-pyrazinedicarboxylic acid dihydrate to the above three-necked round-bottomed glass flask, heat and stir at 42°C for 4 hours, and then cool naturally. The resulting reaction solution is centrifuged at 1350G for 0.5h to remove large particle products, and then the supernatant is centrifuged at 18000G for 5h, and the supernatant is discarded to obtain solid light-controlling particles 23. The solid light-controlling particles 23 are fully dispersed with 250ml of isoamyl acetate.
[0052] Example 2 Preparation of Suspending Medium
[0053] 24.4 g of dodecyl methacrylate, 2.0 g of hydroxyethyl methacrylate, 2.3 g of 1-hexanethiol, and 20 mL of toluene were added to a 250 ml three-necked round-bottomed glass flask. A mechanical stirrer was installed in the middle of the three-necked round-bottomed glass flask, a condenser was connected to one side, and a thermometer was placed on the other side and connected to argon. Before starting heating, argon was passed through the round-bottomed glass flask for about 10 minutes to replace the air in the round-bottomed glass flask. The flask was then heated to 60°C. At this temperature, 10 mL of toluene solution containing 0.20 g of azobisisobutyronitrile was added to the flask. The reaction temperature was maintained at 60°C for a total of 21 hours, and then the reaction temperature was increased to reflux the reaction solution for about 3 hours. Stop the reaction. Then, the toluene and unreacted raw materials were removed by a rotary evaporator at 100°C for 3 hours to obtain a suspension medium.
[0054] Example 3 Preparation of a mixture of a suspension medium containing solid light-controlling particles 23
[0055] In a 250 ml round-bottom glass flask, 40 g of the suspension medium obtained in Example 2 was added, and the isoamyl acetate dispersion of the solid light-controlling particles 23 prepared in Example 1 was added in batches. The isoamyl acetate was removed by a rotary evaporator. Finally, the rotary evaporator was used to continue processing at 80°C for 3 hours to obtain a mixture of the suspension medium containing the solid light-controlling particles 23.
[0056] Example 4 Preparation of a mixture containing a suspension medium containing solid light-controlling particles 23
[0057] Add 40 g of di(2-ethylhexyl) phthalate suspension medium into a 250 ml round-bottom glass flask, and add the isoamyl acetate dispersion of the solid light-control particles 23 prepared in Example 1 in batches. Remove the isoamyl acetate using a rotary evaporator, and finally continue to treat using a rotary evaporator at 80°C for 3 hours to obtain a mixture of the suspension medium containing the solid light-control particles 23.
[0058] Example 5 Preparation of polymer matrix precursor
[0059] Add 54g of hydroxyl-terminated dimethyl diphenyl polysiloxane and 190mL of n-heptane to a 500mL three-necked round-bottomed glass flask. Connect a water separator to a condenser on one side of the three-necked round-bottomed glass flask, install a mechanical stirrer in the middle, and place a thermometer on the other side. Heat the reaction solution in the three-necked round-bottomed glass flask to reflux for 30 minutes. When a small amount of water appears in the water separator, add a solution of 0.13g of stannous octoate dissolved in 10mL of n-heptane. Then add 3g of 3-acryloxypropyl trimethoxysilane dropwise for about 5 minutes. Then condense for 2 hours, and then immediately add 30mL of trimethylmethoxysilane as a terminator for the reaction; terminate the reaction for 2 hours, and then quickly cool to room temperature. Mix 50mL of ethanol and the cooled reaction solution in a 1L beaker, then wash the reaction bottle with 30mL of heptane and pour it into the beaker. After mixing evenly, add 200mL of methanol and stir for 15 minutes. The obtained mixed solution was poured into a 1L separatory funnel and allowed to stand for several hours to separate into layers. The lower layer was taken out and then treated by a rotary evaporator at 70°C for 3 hours to remove low boiling substances, thereby finally obtaining a polymer matrix precursor.
[0060] Example 6 Preparation of polymer matrix precursor
[0061] Same as Example 5, except that 3-acryloxypropyltrimethoxysilane is replaced by 3-methacryloxypropyltrimethoxysilane.
[0062] Example 7 Preparation and voltage resistance test of dimming film
[0063] The initiator for initiating crosslinking and curing of the polymer matrix precursor, the mixture of the suspension medium containing the solid light-controlling particles 23, the polymer matrix precursor and the solid additive 24 are uniformly mixed, and the obtained mixture is called the light-controlling layer matrix emulsion.
[0064] 0.03 g of photoinitiator 819, 3.0 g of the suspension medium containing solid light-controlling particles 23 prepared in Example 3, 7.0 g of the polymer matrix precursor prepared in Example 5 and 0.01 g of solid additive P2015SL-F1-2.5 8-12 μm (purchased from Cospheric) were mixed evenly to obtain a light-controlling layer matrix emulsion.
[0065] The light-controlling layer matrix emulsion was coated on the ITO / PET transparent conductive film with a doctor blade type automatic coating machine (MSK-AFA-III, MTI Corporation) to a thickness of 80 μm, and another layer of ITO / PET transparent conductive film was covered on the light-controlling layer matrix emulsion wet film to obtain a light-controlling layer wet film. Then, the film was cured for 1 minute using an X200-150 UV curing machine produced by Aventk under a nitrogen atmosphere, with a UV power of 700 W / m 2 , the dimming film is obtained.
[0066] In this embodiment, a transparent conductive film (transparent electrode) is formed on a plastic sheet substrate.
[0067] The polymer matrix precursor is crosslinked and cured to form a polymer matrix. Preferably, the polymer matrix is a siloxane copolymer.
[0068] Preferably, the polymer matrix precursor contains cross-linkable functional groups and is cured through a cross-linking reaction to form a polymer matrix.
[0069] Preferably, the polymer matrix precursor is an organic silicone oil containing unsaturated bonds.
[0070] More preferably, the polymer matrix precursor is (meth)acryloxy-modified silicone oil, specifically acryloxy-modified silicone oil and methacryloxy-modified silicone oil in the embodiments of the present invention; the type of polymer matrix precursor can be selected according to actual needs in the present invention, and there is no special limitation. The polymer matrix precursor can also be selected from at least one of Crosile 7270 (acryloxy-functionalized oligosiloxane) produced by Yongxiu County Aikopu New Materials Co., Ltd., UV500 (acrylate-modified silicone oil) produced by Shanghai Buwei Industrial Co., Ltd., and acrylic acid-modified silicone resin produced by Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd.
[0071] The initiator for initiating crosslinking and curing of the polymer matrix precursor is preferably a photoinitiator, and in the embodiment of the present invention, it is specifically a photoinitiator 819. The present invention can select the type of photoinitiator according to actual needs without special restrictions. For example, the photoinitiator can be selected from at least one of 184, ITX, 819, 1173, BDK, BP, TPO, 369, and 907. The mass of the photoinitiator is preferably 0.05% to 1% of the mass of the polymer matrix precursor, more preferably 0.1% to 0.6%, and more preferably 0.2% to 0.5%.
[0072] Therefore, the present application also provides a method for manufacturing a light valve, comprising:
[0073] Providing solid light-controlling particles;
[0074] providing a suspension medium;
[0075] Mixing the solid light-controlling particles with the suspension medium to form a mixture of the suspension medium containing the solid light-controlling particles;
[0076] providing a polymer matrix precursor;
[0077] Mixing an initiator for initiating crosslinking and curing of the polymer matrix precursor, a mixture of the suspension medium containing solid light-controlling particles, the polymer matrix precursor and a solid additive to obtain a light-controlling layer matrix emulsion;
[0078] Applying the light control layer matrix emulsion on the first transparent electrode of the first transparent substrate to form a light control layer wet film;
[0079] The second transparent electrode on the second transparent substrate is covered on the light control layer wet film; the light control layer wet film is cross-linked and cured to obtain Figure 1 The light valve shown.
[0080] The present application uses the relative change rate ΔT of the light valve transmittance T to examine the pressure resistance performance of the light valve.
[0081] Relative change rate of ΔT = [(Ton before compression test - Toff before compression test) - (Ton after compression test - Toff after compression test)] / (Ton before compression test - Toff before compression test) * 100%, where Ton refers to the transmittance of the light valve when it is powered on, and Toff refers to the transmittance of the light valve when it is not powered on. The electric field strength measured by Ton before the compression test is the same as that measured by Ton after the compression test.
[0082] Obviously, the smaller the relative change rate of ΔT is, the better the pressure resistance of the light valve is.
[0083] The light transmittance of the dimming film was measured using a LS116 light transmittance meter (Shenzhen Linshang Technology Co., Ltd.). When no voltage was applied (off state), the light transmittance of the dimming film Toff = 0.5%. When 60 Hz 220V AC was applied (on state), the total light transmittance of the dimming film Ton = 63.2%.
[0084] Compression test:
[0085] The above dimming film was sandwiched between two pieces of glass and subjected to a pressure test in an autoclave. The test conditions were: temperature 110°C, vacuum for 10 minutes, gradually pressurized to 350kPa, delayed for 30 minutes, and then cooled to room temperature to test the change in the transmittance of the dimming film. When no voltage was applied (off state), the transmittance of the dimming film Toff = 0.6%. When 60 Hz 220V AC was applied (on state), the total light transmittance of the dimming film Ton = 61.1%.
[0086] The specific results are shown in Table 1.
[0087] Example 8 Preparation and voltage resistance test of dimming film
[0088] The same as Example 7, except that the mixture of the suspension medium containing the solid light-controlling particles 23 prepared in Example 4 is used instead of the mixture of the suspension medium containing the solid light-controlling particles 23 prepared in Example 3.
[0089] 0.1 g of solid additive P2011SL-2.5 3-6 μm (purchased from Cospheric) was used to replace 0.01 g of solid additive P2015SL-F1-2.5 8-12 μm.
[0090] The specific results are shown in Table 1.
[0091] Example 9 Preparation and voltage resistance test of dimming film
[0092] The same as Example 7, except that the polymer matrix precursor prepared in Example 6 is used instead of the polymer matrix precursor prepared in Example 5.
[0093] The specific results are shown in Table 1.
[0094] Example 10 Preparation and voltage resistance test of dimming film
[0095] Same as Example 7, except that 0.005 g of solid additive P2050SL-F1-2.5 35-45 μm (purchased from Cospheric Corporation) was used instead of 0.01 g of solid additive P2015SL-F1-2.5 8-12 μm.
[0096] The compression test conditions are as follows: temperature 120°C, vacuum for 10 minutes, gradually pressurizing to 500 kPa, and delaying for 30 minutes. The specific results are shown in Table 1.
[0097] Example 11 Preparation and voltage resistance test of dimming film
[0098] Same as Example 7, except that 0.001 g of solid additive SiO2MS-2.0 0.166 μm (purchased from Cospheric Corporation) was used instead of 0.01 g of solid additive P2015SL-F1-2.5 8-12 μm.
[0099] The compression test conditions are as follows: temperature 120°C, vacuum for 10 minutes, gradual pressure increase to 500 kPa, and delay for 30 minutes.
[0100] The specific results are shown in Table 1.
[0101] Example 12 Preparation and voltage resistance test of dimming film
[0102] Same as Example 7, except that 0.65 g of solid additive PMPMS-1.4 3-10 μm (PMMA, polymethyl methacrylate, purchased from Cospheric Corporation) was used instead of 0.01 g of solid additive P2015SL-F1-2.5 8-12 μm.
[0103] The compression test conditions are as follows: temperature 110°C, vacuum for 10 minutes, gradual pressure increase to 800 kPa, and delay for 30 minutes. The specific results are shown in Table 1.
[0104] Example 13 Preparation and voltage resistance test of dimming film
[0105] The same as Example 12, except that 0.1 g of solid additive PMPMS-1.4 3-10 μm (PMMA, polymethyl methacrylate, purchased from Cospheric Corporation) was used.
[0106] The specific results are shown in Table 1.
[0107] Example 14 Preparation and voltage resistance test of dimming film
[0108] The same as Example 8, except that the polymer matrix precursor prepared in Example 6 is used instead of the polymer matrix precursor prepared in Example 5.
[0109] The specific results are shown in Table 1.
[0110] Example 15 Preparation and voltage resistance test of dimming film
[0111] Same as Example 7, except that 0.005 g of solid additive P2015SL-F1-2.5 8-12 μm (purchased from Cospheric) was used.
[0112] The specific results are shown in Table 1.
[0113] Example 16 Preparation and voltage resistance test of dimming film
[0114] Same as Example 7, except that 0.2 g of solid additive P2015SL-F1-2.5 8-12 μm (purchased from Cospheric) was used.
[0115] The specific results are shown in Table 1.
[0116] Example 17 Preparation and voltage resistance test of dimming film
[0117] Same as Example 7, except that 0.4 g of solid additive P2015SL-F1-2.5 8-12 μm (purchased from Cospheric) was used.
[0118] The specific results are shown in Table 1.
[0119] Example 18 Preparation and voltage resistance test of dimming film
[0120] Same as Example 11, except that 0.1 g of solid additive SiO2MS-2.0 0.166 μm (purchased from Cospheric Corporation) was used.
[0121] The specific results are shown in Table 1.
[0122] Example 19 Preparation and voltage resistance test of dimming film
[0123] Same as Example 11, except that 0.65 g of solid additive SiO2MS-2.0 0.166 μm (purchased from Cospheric Corporation) was used.
[0124] The specific results are shown in Table 1.
[0125] Example 20 Preparation and voltage resistance test of dimming film
[0126] Same as Example 10, except that 0.1 g of solid additive P2050SL-F1-2.5 35-45 μm (purchased from Cospheric Corporation) was used.
[0127] The specific results are shown in Table 1.
[0128] Example 21 Preparation and voltage resistance test of dimming film
[0129] Same as Example 10, except that 0.53 g of solid additive P2050SL-F1-2.5 35-45 μm (purchased from Cospheric Corporation) was used.
[0130] The specific results are shown in Table 1.
[0131] Example 22 Preparation and voltage resistance test of dimming film
[0132] The same as Example 10, except that NMHT200 (PS, polystyrene, purchased from Suzhou Nanotech Co., Ltd.) was used instead of P2050SL-F1-2.5 35-45 μm (purchased from Cospheric Corporation).
[0133] The specific results are shown in Table 1.
[0134] Comparative Example 1 Preparation and Voltage Resistance Test of Dimming Film Same as Example 7, except that no solid additive is added.
[0135] Comparative Example 2 Preparation and Voltage Resistance Test of Dimming Film
[0136] Same as Example 8, except that no solid additive is added.
[0137] Comparative Example 3 Preparation and Voltage Resistance Test of Dimming Film
[0138] Same as Example 9, except that no solid additive is added.
[0139] Comparative Example 4 Preparation and Voltage Resistance Test of Dimming Film
[0140] Same as Example 10, except that no solid additive is added.
[0141] Comparative Example 5 Preparation and Pressure Test of Dimming Film
[0142] Same as Example 11, except that no solid additive is added.
[0143] Comparative Example 6 Preparation and Voltage Resistance Test of Dimming Film
[0144] Same as Example 12, except that no solid additive is added.
[0145] Comparative Example 7 Preparation and Voltage Resistance Test of Dimming Film
[0146] Same as Example 13, except that no solid additive is added.
[0147] Comparative Example 8 Preparation and Voltage Resistance Test of Dimming Film
[0148] Same as Example 14, except that no solid additive is added.
[0149] Comparative Example 9 Preparation and Voltage Resistance Test of Dimming Film
[0150] Same as Example 22, except that no solid additive is added.
[0151] Table 1
[0152]
[0153]
[0154]
[0155]
[0156] From the data in Table 1, it can be seen from the comparison between comparative examples 1-9 and embodiments 7-14 and 22 that the scheme of adding solid additives has unexpectedly significant effects on improving the compressive strength of the light-controlling layer, and the relative change rate of ΔT in the embodiments with solid additives is much smaller than that in the comparative examples without solid additives. It can fully meet the lamination process requirements for the subsequent production of dimming glass components.
[0157] In the above embodiments, the solid additives used are solid microspheres, and the sizes in the table are the diameters of the solid microspheres. It is easy for those skilled in the art to understand that solid additives in other shapes are also possible. For example, they can also be solid rods, solid particles, solid fibers, and any other solid materials that can play a compressive role.
[0158] For example, the solid additive may be in a regular shape, such as a microsphere, or in an irregular shape, such as an irregular polyhedron.
[0159] In addition, the solid particles may be polyhedral solid particles in addition to microspheres.
[0160] In addition, in terms of materials, the spherical solid particles include oxide microspheres or polymer microspheres.
[0161] In addition, the solid fibers can be glass fibers, polymer fibers.
[0162] The inventors have found that the solid additive can resist compression in a wide range of sizes. Preferably, the maximum straight-line distance between two points on the surface of the solid additive is less than 50 microns, and more preferably, the maximum straight-line distance between two points on the surface of the solid additive is less than 20 microns.
[0163] As for the additive using microspheres, preferably the diameter of the microspheres may be 0.1 micron to 50 microns, more preferably, the diameter of the microspheres may be 0.5 micron to 20 microns, and further preferably, the diameter of the microspheres may be 1 micron to 15 microns.
[0164] The inventors have found that in terms of the content of solid additives, preferably, the mass of the solid additives accounts for 0.01% to 6% of the mass of the light-controlling layer matrix emulsion, more preferably, the mass of the solid additives can account for 0.03% to 4% of the mass of the light-controlling layer matrix emulsion, and further preferably, the mass of the solid additives can account for 0.08% to 2% of the mass of the light-controlling layer matrix emulsion.
[0165] The solid additives distributed in the polymer matrix play two roles: one is to significantly improve the compressive performance, and the other is to effectively prevent the dimming film from short-circuiting.
[0166] The present invention is described above by taking a light valve with a transparent plastic sheet as a substrate, namely a dimming film, as an example. Obviously, the concept of the present invention is also fully applicable to a light valve with a glass substrate, namely a dimming glass.
[0167] In addition, the present application also provides a dimming glass assembly, including a first glass plate and a second glass plate, and the above-mentioned dimming film is arranged between the first glass plate and the second glass plate; wherein: a first interlayer is arranged between the first glass plate and the above-mentioned dimming film, and / or a second interlayer is arranged between the second glass plate and the above-mentioned dimming film.
[0168] In the present invention, there is no special restriction on the types of the first glass plate and the second glass plate. They can be transparent glass used in conventional dimming glass assemblies well known to those skilled in the art. They can be ordinary glass such as inorganic glass and organic glass, or functional glass such as UV blocking glass, IR blocking glass, Low-E glass, tempered glass or antibacterial glass.
[0169] In the present invention, there is no special restriction on the types of the first interlayer and the second interlayer, which are conventional interlayers for dimming glass components well known to those skilled in the art, and may be EVA films, TPU films, PVB films, or functional films, such as UV-blocking EVA films, UV-blocking TPU films, UV-blocking PVB films, etc.
[0170] In the present invention, the method for manufacturing the dimming glass assembly is not particularly limited, and can be a conventional laminating method of the dimming glass assembly in the art, such as laminating in a laminator, or laminating in an autoclave or a laminating box / furnace.
[0171] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A light valve, characterized in that: include: a first transparent substrate, a first transparent electrode formed on a first transparent substrate, The second transparent substrate, A second transparent electrode is formed on the second transparent substrate, the first transparent electrode and the second transparent electrode are arranged opposite to each other, and A light control layer is disposed between the first transparent electrode and the second transparent electrode; the light control layer comprises a polymer matrix; Wherein, the polymer matrix is dispersed with suspension medium droplets, and the suspension medium droplets are distributed with solid light-controlling particles. A solid additive capable of enhancing the compressive resistance of the light-controlling layer is also distributed in the polymer matrix, and the mass of the solid additive accounts for 0.01% to 6% of the mass of the light-controlling layer matrix emulsion; the solid additive is selected from solid particles; the solid particles include spherical solid particles; the spherical solid particles are microspheres with a diameter of 0.1 microns to 50 microns.
2. The light valve according to claim 1, characterized in that The spherical solid particles include at least one of oxide microspheres and polymer microspheres.
3. The light valve according to claim 1, characterized in that The maximum straight-line distance between two points on the surface of the solid particle is less than 50 microns.
4. The light valve according to claim 3, characterized in that The maximum straight-line distance between two points on the surface of the solid particle is less than 20 microns.
5. The light valve according to claim 1, characterized in that The spherical solid particles are microspheres with a diameter of 0.5 microns to 20 microns.
6. The light valve according to claim 5, characterized in that The spherical solid particles are microspheres with a diameter of 1 micron to 15 microns.
7. The light valve according to claim 1, characterized in that The mass of the solid additive accounts for 0.03% to 4% of the mass of the light control layer matrix emulsion.
8. The light valve according to claim 7, characterized in that The mass of the solid additive accounts for 0.08% to 2% of the mass of the light control layer matrix emulsion.
9. The light valve according to claim 1, characterized in that The polymer matrix is a siloxane copolymer.
10. The light valve according to claim 1, wherein: The material forming the suspension medium droplets includes at least one of fluorocarbon organic compounds, phthalates, trimellitates, dodecylbenzene, polybutene oil, polyacrylate, polymethacrylate, epoxidized soybean oil, and epoxidized linseed oil.
11. The light valve according to claim 1, characterized in that The first transparent substrate and the second transparent substrate include glass plates.
12. The light valve according to claim 1, wherein: The first transparent substrate and the second transparent substrate include transparent plastic sheets.
13. The light valve according to claim 1, wherein: The first transparent electrode includes ITO, nano-Ag wire, conductive graphene, and nano-Cu wire; the second transparent electrode includes one of ITO, nano-Ag wire, conductive graphene, and nano-Cu wire.
14. The light valve according to claim 13, characterized in that The first transparent electrode and / or the second transparent electrode is covered with an insulating layer.
15. A dimming glass assembly, characterized in that: include a first glass plate and a second glass plate, a light valve as defined in claim 12 disposed between the first glass sheet and the second glass sheet; A first interlayer is provided between the first glass plate and the light valve, and / or A second interlayer is disposed between the second glass plate and the light valve.
16. A method for manufacturing a light valve according to any one of claims 1 to 14, characterized in that: include Providing solid light-controlling particles; providing a suspension medium; Mixing the solid light-controlling particles with the suspension medium to form a mixture of the suspension medium containing the solid light-controlling particles; providing a polymer matrix precursor; Mixing an initiator for initiating crosslinking and curing of the polymer matrix precursor, a mixture of the suspension medium containing solid light-controlling particles, the polymer matrix precursor and a solid additive to obtain a light-controlling layer matrix emulsion; Applying the light control layer matrix emulsion on the first transparent electrode of the first transparent substrate to form a light control layer wet film; Covering the light control layer wet film with a second transparent electrode on the second transparent substrate; The light control layer wet film is cross-linked and cured to obtain the light valve.
Citation Information
Patent Citations
Liquid crystal display device and method for producing the same
CN1120177A
Dimming film and preparation method thereof
CN112882258A